2019
DOI: 10.3750/aiep/02616
|View full text |Cite
|
Sign up to set email alerts
|

First results on the diet of the invasive Pterois miles (Actinopterygii: Scorpaeniformes: Scorpaenidae) in the Hellenic waters

Abstract: The diet composition of devil lionfish, Pterois miles (Bennet, 1828), from the Aegean Sea was investigated. The stomach contents of 42 samples (10 of which were empty) collected between May 2016 and November 2017 from Rhodes Island, Greece, were studied. The diet was composed predominantly of bony fish (78.5% in number, approximately 94.7% in biomass) belonging to a large variety of families, and invertebrates (15.4% in number, 5.1% in biomass), thus indicating an opportunistic feeding behaviour of the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Although we did not systematically quantify nocturnal activity, four active Mediterranean lionfish were observed during a pilot observation taken immediately after sunset, indicating individuals may be hunting at night. This hypothesis may be corroborated by the common findings of nocturnal prey species in Mediterranean lionfish stomach contents (Zannaki et al 2019, Nir Stern personal communication) and by studies showing nocturnal behaviour in Red Sea lionfish (Fishelson 1975, McTee & Grubich 2014). However, studies on invasive Atlantic lionfish report little or no nocturnal activity (Green et al 2011, McCallister et al 2018), suggesting potential differences in nocturnal behaviour between lionfish in natal vs invaded habitats.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although we did not systematically quantify nocturnal activity, four active Mediterranean lionfish were observed during a pilot observation taken immediately after sunset, indicating individuals may be hunting at night. This hypothesis may be corroborated by the common findings of nocturnal prey species in Mediterranean lionfish stomach contents (Zannaki et al 2019, Nir Stern personal communication) and by studies showing nocturnal behaviour in Red Sea lionfish (Fishelson 1975, McTee & Grubich 2014). However, studies on invasive Atlantic lionfish report little or no nocturnal activity (Green et al 2011, McCallister et al 2018), suggesting potential differences in nocturnal behaviour between lionfish in natal vs invaded habitats.…”
Section: Discussionmentioning
confidence: 60%
“…High growth rates (up to 20 cm total length [TL] in the first year), large body size (up to 37 cm TL at four years) and early maturation (sexual maturity in less than a year) in Mediterranean lionfish (Kleitou et al 2019), can be expected to translate into rapid rates of population increase (Morris & Whitefield 2009, Edwards et al 2014, Côté & Smith 2018), which is often an essential prerequisite to outcompete native competitors for spaces and resources during the establishment phase of the invasive process (Holway & Suarez 1999, Chapple et al 2012). Moreover, early studies on Mediterranean lionfish stomach contents report that they feed on a wide range of crustacean and fish species (Kleitou et al 2019, Zannaki et al 2019), suggesting they are generalist predators and that they may be well equipped to deal with environmental stochasticity in the invaded region (García-Berthou 2007, Peake et al 2018). However, evidence of dietary specialization on species with particular morphological (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The lionfish pathway invasion along the Levantine coasts and the results of recent genetic studies substantiate the hypothesis that P. miles is a Lessepsian immigrant [61]. In the Aegean Sea, P. miles was firstly recorded from the Kalymnos Island in 2009 and later in 2015 at Rhodes and Crete islands [62]. In only 3 years, the species invaded all the suitable habitats around Rhodes and Crete and extended its distribution to the islands north to Rhodes, to the Cyclades, and, lastly, to the Ionian waters, reaching the border with the Adriatic Sea [14].…”
Section: The Lionfish Pterois Miles (Bennett 1828) (Scorpaenidae)mentioning
confidence: 63%
“…In the Mediterranean, lionfish are mostly found on rocky substrata, followed by seagrass (Posidonia oceanica) meadows [51], and they are also able to occupy deep-water habitats [56] including Dendrophyllia ramea coral communities at 130-150 m depth [57]. The biological studies conducted in the Mediterranean have shown that lionfish have characteristics that are typical of invasive success such as early maturity, rapid growth rates, generalist predation behavior, lack of natural predators, and naïve prey [51,[58][59][60].…”
Section: Results Of the Lionfish Risk And Management Assessmentsmentioning
confidence: 99%